Architectural education according to the didactic thought of Professor Bolesław Szmidt - Jabłoński, Wojciech (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The article presents the views and didactic methods of professor Bolesław Szmidt based on the reports and results of the professor’s work in SARP committees and other sources, and on the basis of didactic materials, student projects developed under the supervision of Bolesław Szmidt. The article uses traditional research methods: analysis of available archival materials, literature studies, and interviews with the associates and graduates of the professor. An attempt was made to characterize the didactic methods and the didactic process in the field of Architecture, which should be applied according to Bolesław Szmidt.